The Determinants of Lecturers’ Classroom Management as Depicted in Their Teaching Performance - Sumekto, Didik Rinan; Setyawati, Heny; Tukiyo; Warsito, Ronggo (Pedagogika, 2020)
This study aims at assessing four determinants of lecturers’ classroom management practices, in which 215 or 18.69% respondents participated in this study. Data analyses used descriptive statistics, Pearson correlations and regression analysis with the significance level of .05. The results showed that the conduciveness (t = 2.992; p = .003), diversity acceptance (t = 3.243; p = .001), disciplines engagement (t = 3.968; p = .000), and corrective decision (t = 3.045; p = .003) partially contributed positive and significant influence towards lecturers’ 28.8% teaching performance, where F = 21.209; R² = .288; p < .000. The analysis discloses two-tailed regression with Y = 12.660 + .225X1 + .175X2 + .237X3 + .142X4.